2017
DOI: 10.1108/rpj-09-2015-0116
|View full text |Cite
|
Sign up to set email alerts
|

Investigating impact of five build parameters on the maximum flexural force in FDM specimens – a definitive screening design approach

Abstract: Purpose The purpose of this study was to examine the impact of five key build parameters – layer thickness, deposition angle, infill, extrusion speed and extrusion temperature, and their interactions – on the maximum flexural force in specimens which are made of polylactic acid (PLA). Design/methodology/approach Through a previous study on the flexural properties of PLA specimens, a statistically significant effect of layer thickness was indicated, requiring further experimentation to establish the values of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(25 citation statements)
references
References 22 publications
0
21
0
Order By: Relevance
“…All the other samples showed a higher central deflection compared to the triangle pattern and performed similarly concerning their corresponding central deflection. 73 The maximum central deflection was shown by the octet sample of up to 33 mm.…”
Section: Resultsmentioning
confidence: 90%
“…All the other samples showed a higher central deflection compared to the triangle pattern and performed similarly concerning their corresponding central deflection. 73 The maximum central deflection was shown by the octet sample of up to 33 mm.…”
Section: Resultsmentioning
confidence: 90%
“…Therefore, ERTAY et al [40] develop a control algorithm that leads to a more uniform material deposition rate and thus to more precise components by influencing the extrusion parameters. LUZANIN et al [41], on the other hand, optimise process parameters for polylactide (PLA) components with the aim of achieving the greatest possible bending strength.…”
Section: Plastic-based Processesmentioning
confidence: 99%
“…It was also found that reduction in voids near the edge was affected by a variety of external perimeters and consequently increased the flexural strength [ 20 ]. Luzanin et al [ 21 ] have studied the influence of raster angle, layer height, percentage infill, extrusion temperature, and speed on the flexural behavior of the PLA parts. They reported the highest flexural strength at 0° raster angle.…”
Section: Introductionmentioning
confidence: 99%